Former prisoners between non-category and invisibility: The Romanian experience - Durnescu, Ioan (Probation journal, 2020)
In this study, we examine the re-entry of 58 people during the first year following their release from prison. Our objective was to gain a more comprehensive perspective on the experience of release from a Romanian prison. We take into account three important dimensions that set the tone and tenor of life after prison: (1) the state as a truant agent in the process of release, (2) family, and (3) employment and other means of becoming economically active, such as hustling (Thieme, 2018) or foraging (Sugie, 2018). We argue that the existent re-entry legislation (or lack thereof) coupled with the way policymakers define the notion of personhood for the former inmate embarks prisoners on a journey widely disconnected from their relevant social contexts. As a consequence, the challenges associated with re-entry are disregarded, and prisoners, once released, become invisible or a ‘non-category’. Successful re-entry, we argue, is a personal accomplishment in the face of adversities, rather than a feasible outcome afforded by structural conditions.